O wybranych mechanizmach kondesacji treści w przekazach medialnych - Grzelka, Monika (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2013)
This article revolves around research into the language of the media with special emphasis placed on a description of the fundamental mechanisms of condensing content in printed and audio and visual media. Condensation is among the basic tools of content accumulation; it is related to simplifying the message, generalization and stylistic deformations. Mechanisms applied to summarize have been identified within various areas, including construing messages and releasing to media as well as modes of organizing the content. Of importance here is the trend of replacing verbal messages with visual messages (tables, photos, information graphics, charts, coverage). While condensation is reflected in media as a communication-related activity strictly functionalized within a message, in its structure (cf. the summarizing role of titles, leads, visualizations), it is also conditioned by genre-related issues (cf. news, previews etc.) and most times results from the broadcaster’s strategic efforts.